Spatial query retrieval model by single measure similarity (SMSS) - Lau, Bee Theng (Faculty of Computer Science and Information Technology, 2006)
Structural spatial query is an active research area in spatial databases. The assessment of structural spatial query similarity is called structural similarity, also known as configuration similarity. This research developed a structural Spatial Query Retrieval Model for spatial databases by Spiral Web representation. The Spiral Web representation model is able to represent the unique relations among query objects in a structural spatial query like neighborhood relation, relative distance, relative direction and object geometry.